2019
DOI: 10.1073/pnas.1905149116
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput system to identify inhibitors of Candidatus Liberibacter asiaticus transcription regulators

Abstract: Citrus greening disease, also known as huanglongbing (HLB), is the most devastating disease of Citrus worldwide. This incurable disease is caused primarily by the bacterium Candidatus Liberibacter asiaticus and spread by feeding of the Asian Citrus Psyllid, Diaphorina citri. Ca. L. asiaticus cannot be cultured; its growth is restricted to citrus phloem and the psyllid insect. Management of infected trees includes use of broad-spectrum antibiotics, which have disadvantages. Recent work has sought to identify sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Furthermore, the latter approaches are laborious and time-consuming, and hence not suitable for high-throughput studies 65,68,69 . Researchers have also resorted to using distantly related microbes as surrogates [74][75][76][77] . However, these results may or may not be reliable or extrapolatable to the target pathogen, owing to differences in pathosystems and virulence mechanisms (or lack thereof).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the latter approaches are laborious and time-consuming, and hence not suitable for high-throughput studies 65,68,69 . Researchers have also resorted to using distantly related microbes as surrogates [74][75][76][77] . However, these results may or may not be reliable or extrapolatable to the target pathogen, owing to differences in pathosystems and virulence mechanisms (or lack thereof).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few groups have studied C Lso root infections, but the levels and distribution of C Lso are greater in roots than shoots, much as for C Las 91 . Given the significance of roots to C Las and C Lso pathology, we posit that the hairy-root-based bioassays described here are more biologically relevant than surrogate pathogen and/or axenic culture systems 74 76 . This is also underscored by reproducible screening results with Arabidopsis NPR1 , and a broad-spectrum bactericide (tetracycline) (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Tolfenamic acid targeting the transcription factor PrbP showed inhibitory activity against CLas in planta in the greenhouse and led to a significant reduction in CLas populations with improved root growth and foliage appearance when applied by foliar spray and root soaking at 100 μM (Gardner et al 2016). Barnett et al (2019) developed a high-throughput screening system to identify compounds that inhibit the transcription activators LdtR, RpoH, and VisNR in CLas (Barnett et al 2019). These regulators are suggested to be essential for CLas motility and cell wall biogenesis (LdtR) (Pagliai et al 2017), stress tolerance (RpoH) (Barnett et al 2019), and colonization of the psyllid vector (VisNR) (Andrade and Wang 2019).…”
Section: Strategies Targeting the Pathogen Clasmentioning
confidence: 99%
“…Barnett et al (2019) developed a high-throughput screening system to identify compounds that inhibit the transcription activators LdtR, RpoH, and VisNR in CLas (Barnett et al 2019). These regulators are suggested to be essential for CLas motility and cell wall biogenesis (LdtR) (Pagliai et al 2017), stress tolerance (RpoH) (Barnett et al 2019), and colonization of the psyllid vector (VisNR) (Andrade and Wang 2019). Over 120,000 compounds were evaluated via this screening system, and several dozen compounds inhibited regulator activity but not CLas growth.…”
Section: Strategies Targeting the Pathogen Clasmentioning
confidence: 99%
“…ZINC05491830 is one of the most potent inhibitors of CLas Esbp, with an IC50 value of 2.59 µM [19]. ChemDiv C549-0604 is an inhibitors of CLas VisNR, with an IC50 value of 0.7 µM [18]. The inhibition assay suggested that the K i values of bronopol and disulfiram were 234 and 616 nM, respectively.…”
Section: Inhibitory Assay Against Clas Impdh∆98-201 Activitymentioning
confidence: 99%